Language acquisition of children aged 2 years in "Kimono mom" YouTube channel - Siti Muharami Malayu; Hanafi Wijaya; Yuddi Adrian Muliadi (JOALL (Journal of Applied Linguistics and Literature), 2023)
This research discusses the language acquisition of 2-year-old children in terms of phonology and syntax. The purpose of this study is to describe the language acquisition in terms of phonology and syntax of 2-year-old children in Kimono Mom YouTube channel episode 1 to 4. The data source of this research is "Kimono Mom" YouTube channel, episode 1 to episode 4 and the data in the study are utterances expressed by a Japanese child named Sutan who lives with his father and mother in Tokyo, Japan. In his daily life Sutan often communicates with his parents, especially with his mother named Moe. This research is descriptive qualitative research with the method of note taking method and library research. The theory used is the theory of language acquisition in terms of phonology and syntax. The results show that in terms of phonology Sutan can pronounce all vowel sounds except the vowel sound [ɯ]. Sutan can pronounce all consonant sounds perfectly except consonant sounds [ŋ], [ʦ] and [ʣ], as well as consonant sound [ʤ] located at the beginning of the word. In addition, Sutan can pronounce all the special phoneme sounds of Japanese except the double vowel sound (chou boin). In terms of syntax, Sutan can pronounce declarative, imperative, interrogative, and exclamative sentences according to the context even though they are in the form of short sentences and still rarely use particles and the sentence only reaches the verb.